2023
DOI: 10.3390/biology12040610
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Human Activities, the Significant Dynamic Drivers of Himalayan Goral Distribution (Naemorhedus goral)

Abstract: The distribution of large ungulates is more often negatively impacted by the changing climate, especially global warming and species with limited distributional zones. While developing conservation action plans for the threatened species such as the Himalayan goral (Naemorhedus goral Hardwicke 1825; a mountain goat that mostly inhabits rocky cliffs), it is imperative to comprehend how future distributions might vary based on predicted climate change. In this work, MaxEnt modeling was employed to assess the hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Similarly, Jiang (2018), and Chen et al ( 2023) observed that the driest months' precipitation exerted a notable in uence on the distribution of endemic, rare, and threatened species, similar to our ndings. This is corroborated by numerous other investigations, e.g., for Pygathrix cinerea (Tran et al, 2018); Himalayan Goral (Haq et al, 2023), Red panda (Thapa et al, 2018) and Tragopan melanocephalus (Jameel et al, 2023). The second most important variable was bio19 (coldest month precipitation), the third elevation, and the fourth was bio08 (wettest quarter mean temperature).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, Jiang (2018), and Chen et al ( 2023) observed that the driest months' precipitation exerted a notable in uence on the distribution of endemic, rare, and threatened species, similar to our ndings. This is corroborated by numerous other investigations, e.g., for Pygathrix cinerea (Tran et al, 2018); Himalayan Goral (Haq et al, 2023), Red panda (Thapa et al, 2018) and Tragopan melanocephalus (Jameel et al, 2023). The second most important variable was bio19 (coldest month precipitation), the third elevation, and the fourth was bio08 (wettest quarter mean temperature).…”
Section: Discussionsupporting
confidence: 81%
“…The Zanskar Range experiences a considerable range in minimum and maximum rainfall, varying from 32 mm to 546 mm annually. This uctuation in precipitation is vital for the ecological dynamics and sustenance of the Hangul population (Haq et al, 2023).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate prediction of species distribution models requires more comprehensive and better distributed occurrence records of species (Feeley & Silman, 2011 ; Hernandez et al., 2006 ). Meanwhile, ecological interactions, dispersal capacity, and habitat preferences all affect the accuracy of modeling results (Haq et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of medicinal plants within semi-arid regions has been a noteworthy practice. These regions, characterized by limited water availability and challenging climatic conditions, have witnessed the persistent use of indigenous plant species for therapeutic purposes Waheed et al 2023;Haq et al 2023b). The traditional knowledge surrounding these plants passed down through generations, holds a rich repository of healing wisdom (Haq et al 2023c).…”
Section: Introductionmentioning
confidence: 99%